Usability Testing Aplikasi Media Pembelajaran IPA Bagi Siswa Sekolah Dasar - Pranatawijaya, Viktor Handrianus; Christian, Efrans (Journal of Information Technology and Computer Science, 2023)
In improving the quality of education, various breakthroughs are needed in curriculum development, learning innovation, fulfillment of educational facilities, and infrastructure to improve learning achievement. One of the innovations in learning, especially in science (Natural Science) subjects at State Elementary School 3 Kalahien Village, is the use of learning media applications with classroom action research methods (Classroom Action Research) to improve student learning. This application uses a smartphone as a learning resource. To find out whether the user can easily use the application so that it can help the user achieve his goals and whether the user is satisfied with the application used, it is necessary to do usability testing. The purpose of this study was to measure the level of usefulness of science learning media applications for SDN 3 Kalahien Village. Measurement of the level of usability is carried out using instruments that are distributed to application users. The system usability scale (SUS) method is used to measure usability. The results showed that 76.25% of this system was well received by users, with an acceptable range falling into the acceptable category and category B for the grade scale with an excellent rating.